Keunikan Penamaan Jurnal Perpustakaan dan Informasi PTKIN: Kajian Semantik - Kardi, Kardi; Ulumi, Bahrul (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2021)
Introduction. This article describes the names of scientific publications journals in the field of libraries and information, which are increasing in number, and the increasing activity of publishing scientific works that encourage librarians to develop writing habits.Methodology. This article employs a qualitative descriptive semantic approach by using various multi-site names of library journals and information in the PTKIN environment. The focus of this paper lies in the uniqueness of naming library and information journals in the PTKIN environment.Results and discussion. The results showed that the journal's name contains terms derived from Indonesian, local languages, and foreign languages. In addition, there is also the name of the journal, which is an abbreviation of letters that makes it easy to recognize.Conclusion. The names of library and information journals in the PTKIN environment tend to contain the meaning of university libraries in a general sense or things related to library materials.